Renal cell carcinoma - epidemiology, risk factors, diagnosis and treatment - review article - Orczykowski, Maciej; Tyszkiewicz, Marcin; Rosińska, Agata; Pożarowska, Kinga; Miga, Nadia (Journal of Education, Health and Sport, 2022)
INTRODUCTION: Renal cell carcinoma (RCC) is the most common urological malignancy. It accounts for 2% of deaths from all malignancies. Most cases of renal cell carcinoma are diagnosed incidentally during routine ultrasound or CT scans. Most cases are diagnosed in the asymptomatic stage. The presence of symptoms such as lower extremity edema and varicose veins of the seminal vasculature usually indicate the presence of an advanced neoplastic process. PURPOSE OF THE WORK: In this article we reviewed the literature on renal cell carcinoma. We collected and compared information on the epidemiology of risk factors, histological classification and treatment of RCC. STATUS OF KNOWLEDGE: According to GLOBOCAN data, there is an increase in the incidence of RCC in developed countries. In the treatment of renal cell carcinoma, the method of choice is surgical excision of the tumor. A kidney-sparing approach is preferred if the conditions exist. VEGF inhibitors, tyrosine kinase inhibitors and m-TOR kinase inhibitors are used in the treatment of metastatic renal cell carcinoma. CONCLUSION: Renal cell carcinoma is the most common urological cancer. By promoting healthy lifestyles, patients can significantly reduce their risk of developing it. The method of choice for treatment is still surgical excision of the tumor.